Advantages and disadvantages of ICASA's 2011 spectrum licensing models - Kedama, Yolisa (My University, 2015)
The challenges of the broadband divide between rural and urban areas, and the demand for access spectrum exceeding the available supply, require regulators to rethink their approaches to spectrum regulation. Traditional spectrum management mechanisms resulted in artificial spectrum scarcity and hoarding whilst operators ignored their universal service obligations. This research report uses the regulatory impact assessment methodology to investigate what the proposed market-based spectrum licensing models of wholesale open access and managed spectrum park mean and the impact such regulatory approaches would have on the communications industry and technology progression. The findings of this research indicate that the wholesale open access and managed park are new concepts and were not well defined thus as a result are not well understood within the industry. The different stakeholders have different interpretations that suit and benefit their own organisations. The regulator does not have spectrum strategy that acts as a guide in achieving a digital country. There is no guiding document that promotes compliance for the relevant stakeholders to roll out broadband networks for next generation e-services. The „artificial‟ interdependence between policy-maker and regulator‟s mandates has created a vacuum where all the industry players manipulate both institutions in order to advance their commercial business interests. Yet, regulatory failure has negative consequences for technology progression. ICASA‟s lack of regulatory impact assessment (RIA) studies worsens the situation as the 2011 proposed spectrum licensing models were never investigated before being introduced. The conclusions of this research indicate that for greater broadband inclusivity, a hybrid of traditional spectrum management approaches with market-based models should be employed. The regulator needs to make RIA a permanent process in decision making to minimise possibilities of 3 litigation and regulatory capture. This will make it easier to implement new regulations and make decisions from an informed position. Incumbents have existing infrastructure, capital and technical expertise and it is up to the regulator to decide whether they can be used as enablers or considered obstacles for faster broadband rollout.
Thesis (M.M. (ICT Policy and Regulation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2014.